Efeito em curto prazo da corrente interferencial associado a cinesioterapia no tronco de paciente com acidente vascular encefálico - Andrade, Daniela da Costa Maia de (2018)
Introduction: Among the main causes of disability associated with stroke, are: impairment of voluntary movements, spasticity, pain and loss of selective activity of muscles responsible for trunk control. The use of interferential current (IFC) in stroke patients has been recently reported in the literature for managing pain and spasticity. Aims: 1. to identify the evidence from studies evaluating the effects of IFC in patients with central neurological diseases (a systematic review); 2. To determine the short-term effect of IF associated with kinesiotherapy on pain of stroke patients; 3. To investigate the short term effects of IFC associated with kinesiotherapy on motor performance and functional gains of the trunk of patients with stroke. Methods: 1) A systematic review of clinical trials on 8 databases (Medline, Scopus, Science Direct, Web of Science, CINAHL, Scielo, Cochrane Central Register and PEDro) was conducted by two investigators by using the following key-words: interferential current OR interferential current therapy OR interferential electrical stimulation OR interferential electrical stimulation therapy OR interferential therapy OR interferential stimulation. The Cochrane collaboration tool was used for methodological quality analysis. 2 and 3) A randomized, double-blinded, placebo-controlled, crossover-type clinical trial was performed. 36 stroke patients were recruited and randomly included in one of two groups: active IFC group (IFC application + kinesiotherapy of trunk) and placebo IFC group (30 minutes of placebo IFC + kinesiotherapy of trunk). Both groups received 10 session of treatment, twice a week, for 60 minutes, with 05 sessions at each treatment group and a washout period of one week between treatments. Results: 1) 2004 studies were found, but only two were included based on the proposed inclusion criteria. After one single session, IFC was effective in reducing pain and spasticity and at improving balance, gait and range of motion of stroke patients. 2 and 3) there was improvement in pain during movement, pain catastrophizing and reaching of the affected member, when comparing pre and post treatment averages. There was no change in fatigue, self-esteem, motivation, trunk control, posture, flexibility and muscle tone in both groups. Conclusion: IFC might have influenced the improvements in trunk control and motor performance of stroke patients when associated with kinesiotherapy. It is recommended that new studies with a higher number of sessions be conducted to better clarify the effects of IFC associated with kinesiotherapy.